Effectiveness of Narrow versus Wide Chest Tube Drainage in Treating Malignant Pleural Effusion - Muhammad Anosh; Khan Afridi, Muhammad Asif (Indus Journal of Bioscience Research, 2025)
Background: Pleural effusion, characterized by the abnormal accumulation of fluid within the pleural space, is a common manifestation of various pleural diseases. It can result from increased fluid production or impaired lymphatic drainage. Management strategies often involve therapeutic interventions such as thoracentesis, repeated drainage procedures, pleurodesis, or insertion of indwelling pleural catheters. Objective: To determine the effectiveness of Narrow versus Wide Chest Tube Drainage in Treating Malignant Pleural Effusion. Methodology: The current Randomized controlled trial was carried out at the Department of Pulmonology, HMC Peshawar from 10th march 2025 10th June 2205. A total of 60 patients were enrolled with 30 patients allocated to each group A and B. Outcome measures were duration of tube placement, recorded in days, and pain assessments was conducted at various time points using a Visual Analog Scale (VAS) to measure pain levels. Data analysis was performed using SPSS version 22. Mean ± standard deviation was calculated for continuous variables like age, pain score, and duration of tube placement. A categorical variable such as gender and residence was analyzed using frequency distributions and percentages. Results: In group A, the male and female patients were 18 (60%) and 12 (40%) respectively while in group B, the male patients were 17 (56.67%) and female patients were 13 (43.33%). The mean (±SD) age in group A was 45 (±3.44) while in group B it was 46 (±2.97). The means (±SD) VAS (24 h) score in group A was 1.49 (± 3.11) while in group B, it was 4.11 (± 2.01) (p=0.001). The means (±SD) Tube Duration (days) in group A was 11.99 (± 3.22) days while in group B, it was 7.01 (± 2.32) days (p=0.001). Conclusion: According to our research, small-bore chest tubes considerably reduce the level of pain when compared to large-bore tubes. Small-bore tubes usually need more time to place, although overall complication rates are comparable. The results of this research suggest that small-bore chest tubes should be the first choice for treating malignant pleural effusions.